“I’d Rather Have Something than Nothing”: Presence and Absence in the Records of Transracial, Transnational Adoptees - Ballin, Mya (Archivaria)

(untitled) (Association of Canadian Archivists, 2023)
In the last decade, archival scholars have begun to deeply reflect upon the experiences of individuals and communities as they interact with administrative and bureaucratic records. They have found that there is a significant gap between the emotional experiences of records activators and the preparedness of archival repositories to address these experiences. Emerging from these realizations is a call for archivists to better understand the experiences of the personal in the bureaucratic and to design and take up reparative, caring, and rights-based frameworks to respond to these previously unaddressed needs. Drawing on semi-structured interviews conducted as part of the author’s master’s thesis, this article maps out connections between transracial, transnational adoptee experiences and ideas about the archival imaginary. In addition to acting as a space for participants to share their stories – which directly demonstrate the ability of records to both create and collapse space for unanswerable questions – this work seeks to take up existing calls to archivists and recordkeepers to consider the impact of the bureaucratic on the personal and to recognize the urgent necessity of addressing these experiences as we move forward into more caring practice.